STRATEGI OPTIMASI DALAM MENENTUKAN LINTASAN TERPENDEK UNDIVIDED RAGNAROK ASSAULT PROBLEM (UNDIVIDED GAMES) - Faisal Piliang; Silvester Dian Handy Permana (Sekolah Tinggi Teknik - PLN, 2015)
The research purpose is to help the end user which is the Undivided Ragnarok players to solve Minimum spanning tree (MST) of a journey from the player’s city to attack monsters in another place by using a graph. The Kruskal algorithm is often used to solve the graph problem of the Minimum spanning tree (MST). The minimum spanning tree (MST) problem is how to select or specify the minimum cost of a minimum spanning tree (MST) of each segment (edge) of a graph that does not form as a circuit, but form as a tree. The conclusion of this research is that the aspects of the graph on the Kruskal algorithm can be applied to solve the shortest path of a journey from the player’s city to attack monsters in another place by obtaining a minimum value of 2550 zeny.